Vitamin D status and insulin sensitivity are novel predictors of resting metabolic rate: a cross-sectional analysis in Australian adults - Calton, E.; Pathak, K.; Soares, Mario; Alfonso, H.; Keane, Kevin; Newsholme, Philip; Cummings, N.; Chan She Ping-Delfos, W.; Hamidi, A. (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2015)
Purpose - Resting metabolic rate (RMR) accounts for two-thirds of the total energy expenditure in sedentary individuals. After accounting for traditional factors, there still remains a considerable unexplained variance in RMR. There is a pandemic of obesity and metabolic syndrome (MetS) which coexists with a high prevalence of vitamin D insufficiency. The aim of this study was to evaluate the potential effects of vitamin D status, insulin sensitivity (IS) and the metabolic syndrome (MetS) on RMR in Australian adults. Methods - RMR, respiratory quotient (RQ), McAuley’s insulin sensitivity index, fat mass (FM), fat-free mass (FFM) and vitamin D status were assessed in Australian adults. The presence of MetS was evaluated by current standard criteria. Predictors of RMR were examined through multiple linear regression based on stepwise and backward regression approaches with attention to multi-collinearity. All analyses were conducted on SPSS version 21. Results - One hundred and twenty-seven participants (45 men, 82 women), aged 53.4 ± 11.7 years and BMI 31.9 ± 5.2 kg/m2, were included. Forty-one subjects were insufficient in vitamin D status (<50 nmol/L), and 75 participants had the MetS. A parsimonious regression model explained 85.8 % of RMR and was given by: RMR (kJ/d) = 1931 + 83.5 × FFM (kg) + 29.5 × FM (kg) + 5.65 × 25(OH)D (nmol/L) − 17.6 × age (years) − 57.51 × IS. Conclusion - Vitamin D status and IS are novel independent predictors of RMR in adults. Future studies could validate a causal role for these factors in human energy metabolism.